Patterns of concomitant traumatic brain injury and ocular trauma in US service members - Weidong Gu; Lucas L Groves; Scott F McClellan
Background Concomitant traumatic brain injury (TBI) and ocular trauma (OT) are caused by the same physical mechanisms, which may complicate therapeutic intervention if screening and evaluation of each condition are not promptly initiated. The aim of this study is to identify concomitant TBI in OT patients and characterize the pattern of those injured service members (SMs) in non-combat environments to assist in the early detection and treatment of both TBI and OT.Methods Encounters matching the case definitions of TBI and OT for injured SMs were extracted from the Military Health System. Concomitant TBI and OT was identified as patients who were diagnosed with both medical conditions within 30 days. Incidence rates of concomitance were analyzed using a Poisson regression model. The odds of mechanisms and types of OT with concomitant TBI were analyzed using logistic regression models.Results From 2017 to 2021, there were 71 689 SMs diagnosed with TBI, and 69 358 patients diagnosed with OT. There were 3251 concomitant cases identified. The overall concomitance rate in OT patients was 4.7%. Clinical presentations of concomitant OT had a higher rate of complications. Blast, transport accidents, assaults, alcohol, falls, and sports-related injuries (in decreasing order) were significantly associated with concomitance rates. Compared with closed globe injuries, OT with orbital fractures, rupture, laceration, adnexal periocular injury, and penetrating injury had higher risks of concomitant TBI. For patients with orbital fractures, nearly half (44.1%) sustained a concomitant TBI.Conclusions A practical approach using temporal proximity of diagnostic data was developed to identify concomitant cases of TBI and OT which presented with more severe injury types than non-concomitant cases. These results indicate OT patients with orbital or open globe injuries sustained from high-impact mechanisms warrant further TBI screening to prompt early detection and treatment.Level of evidence IV.